2018
DOI: 10.1177/1049909118806456
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Chart Review of Transfusion Practices in the Palliative Care Unit Setting

Abstract: Background: There remains limited data in the literature on the frequency, clinical utility and effectiveness of transfusions in palliative care, with no randomized controlled trials or clinical practice guidelines on this topic. There are no routinely accepted practices in place for the appropriate transfusion of blood products in this setting. Aim: The aim of this study was to retrospectively review all transfusions in the palliative care units of 2, tertiary care hospitals in Canada. The goals were to eluci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 16 publications
5
10
5
Order By: Relevance
“…Neoh et al [11] report that 70% of patients had an Hb above the trigger threshold of 7.0 g/dL, while we found an inferior frequency of 42%. Also, we found a median of RBC units given per TE (1.0) similar to Sirianni et al [15] and lower than Neoh et al [11] (2.0) and Timothy et al retrospective [10] (2.3) and prospective [3] (2.1) studies. These results may re ect doctors' effort to adopt a restrictive blood transfusion strategy in a PC setting.…”
Section: Discussion Clinical Practicessupporting
confidence: 82%
See 2 more Smart Citations
“…Neoh et al [11] report that 70% of patients had an Hb above the trigger threshold of 7.0 g/dL, while we found an inferior frequency of 42%. Also, we found a median of RBC units given per TE (1.0) similar to Sirianni et al [15] and lower than Neoh et al [11] (2.0) and Timothy et al retrospective [10] (2.3) and prospective [3] (2.1) studies. These results may re ect doctors' effort to adopt a restrictive blood transfusion strategy in a PC setting.…”
Section: Discussion Clinical Practicessupporting
confidence: 82%
“…We found a mean pretransfusion Hb level of 6.85 g/dL, lower than Neoh et al [11] (7.5 g/dL) and Timothy et al retrospective [10] (7.8 g/dL) and prospective [3] (7.2 g/dL) studies but higher than Sirianni et al [15] (6,5 g/dL). Neoh et al [11] report that 70% of patients had an Hb above the trigger threshold of 7.0 g/dL, while we found an inferior frequency of 42%.…”
Section: Discussion Clinical Practicescontrasting
confidence: 73%
See 1 more Smart Citation
“…Those previous studies showed a great variability in the platelet transfusion burden at the end‐of‐life. Whereas no platelet units were issued per patient in a palliative care unit [8], a median of 11·57 was issued in intensive care units or haematology departments [9]. This variability also concerned the symptom burden, ranging from zero in a palliative care unit [8] to 60% (with 20% of grade 4) in intensive care units or haematology departments [9].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas no platelet units were issued per patient in a palliative care unit [8], a median of 11·57 was issued in intensive care units or haematology departments [9]. This variability also concerned the symptom burden, ranging from zero in a palliative care unit [8] to 60% (with 20% of grade 4) in intensive care units or haematology departments [9]. Prophylactic transfusions, which are valid [10] although debated [4, 5, 11], were almost regular practice [12].…”
Section: Introductionmentioning
confidence: 99%